The acute effects of light versus heavy - load back squats on speed-power performance among amateur male rugby players / Muhammad Aiman Muhammad - Muhammad, Muhammad Aiman (2021)
Post-activation potentiation (PAP) warm-up such as back squat, can improve speed-power performance. However, the prescribe intensity is not clearly determined. The aim of this study was to investigate whether performing light-load back squat (LS) versus heavy-load back squat (HS) as PAP warm-up exposure prior sprinting activity able to improve speed-power performance among amateur male rugby players. Twenty three amateur male rugby players (age: 20.7 ± 1.4 years; BMI 22.5 ± 1.7 kg.m-2) from various rugby teams around Alor Setar, Kedah were recruited in this study. This study was a repeated-measures study design consisted of control and two PAP warm-up exposures. Participants exposed to three trials; control trial with no PAP warm-up (C), light-load back squat (LS = 60% of 1RM), and heavy-load back squat (HS = 85% of 1RM). During each trial, participants performed warm-up on stationary bike at 60 rpm for 6 minutes and followed by prescribed warm-up exposure before proceeding to 40-meter sprint test with 4 minutes rest in between activities. Participants performed all warm-up exposures with two sets of four repetitions in three non-consecutive days of trials within two weeks. The 40-meter sprint test was used to measure speed-power performance during the trials. The data was analysed by using one-way ANOVA with repeated-measures. As a result, sprinting time had improved significantly (p<0.001) after LS (-11.91%), and HS (-18.03%) PAP warm-up when compared to control. When compared between two PAP warm-ups, HS was significantly superior to LS (p<0.001) with 6.95% v improvement in sprinting time. In conclusion, the present study found that performing back squat PAP warm-up with sub-maximal load; two sets of four repetitions prior sprinting activity able to improve speed-power performance with heavy-load back squat having a superior effect among amateur male rugby players.